Measurements of ethanol uptakes on activated carbon - Tan, Alex Kai Yi (2014)
Due to global warming and ozone depleting potentials impacts on the environment, there is an urgent need in search for efficient and green technologies. In recent years adsorption chillers becomes popular and soon will be replacing vapor compression based chillers. For this project, the measurement of the ethanol uptakes on activated carbon is investigated at isothermal conditions i.e. various pressures and temperatures. A setup of a Constant Volume Variable Pressure (CVVP) apparatus was used in this experiment to measure the amount of ethanol uptakes on activated carbon and the uptakes are measured in terms of pressure, temperature and volumes. The volume calibration for CVVP was performed to carry out the volume calibration of the dosing and charging chambers of the set-up. The isotherms used for the experiments are 303K, 313K, 323K, 328K and 333K and the pressures are varied up to 5 kPa. The amount of ethanol uptakes are calculated employing the ideal gas equation. The experimentally measured data are compared and validated with existing adsorption isotherm models such as Langmuir, Tóth and Dubinin-Astakhoy. The experimental results conclude that the maximum adsorption occurs at low temperature and high pressure. Comparing the isotherm equations with the experimental data, it is found that Tóth isotherm shows the lower RMSE values.